The role of maturation in upper-limb plyometric vs. technical plyometric training for youth badminton players - Shi, Yujie; Yi, Mingbing; Cai, Ruibao; Li, Han; Luo, Danni; Yu, Mengjie (Frontiers in Physiology, 2026)
BackgroundPlyometric training may enhance upper-limb explosive performance and stroke velocity in youth badminton players while contributing to mitigate injury risk, yet the influence of biological maturation on these adaptations remains unclear.PurposeTo compare the effects of upper-limb plyometric training (PLYOgen), technical plyometric training integrating badminton stroke mechanics (PLYObad), and regular training on upper-limb strength, plyometric performance, and smash speed while accounting for maturity offset.MethodsSixty-two male players (12–14 years) were randomized to PLYOgen, PLYObad, or control. All groups continued their usual badminton practice (2–3 sessions/week; 75–90 min/session). Over 6 weeks, only the intervention groups completed an additional supervised plyometric session once per week (25–30 min; 72 explosive actions), whereas the control group performed no additional plyometric/strength sessions. Repeated-measures ANCOVA with maturity offset as covariate assessed pre–post changes in overhead medicine ball throw, seated chest pass, plyometric push-up height, and smash speed.ResultsSignificant time effects were observed for all outcomes (p < 0.001; η2p = 0.737–0.954). Time × maturity-offset interactions were significant for overhead throw (p < 0.001; η2p = 0.571), chest pass (p < 0.001; η2p = 0.482), push-up height (p = 0.006; η2p = 0.122), and smash speed (p < 0.001; η2p = 0.360), indicating that players with higher maturity offset (closer to or beyond PHV) tended to show larger pre–post improvements. Time × group interactions were also significant for overhead throw (p < 0.001; η2p = 0.918), chest pass (p < 0.001; η2p = 0.840), push-up height (p < 0.001; η2p = 0.718), and smash speed (p < 0.001; η2p = 0.950). Post-hoc analysis showed PLYOgen and PLYObad improved overhead throw and smash speed more than control, with PLYOgen also presenting greater values than control in push-up height.ConclusionBoth plyometric approaches enhanced upper-limb explosive performance, with biological maturation significantly moderating training responsiveness. This should be considered when modifying youth training programs to manage injury risk factors and to ensure that training practices are appropriately aligned with the players’ developmental level.